Cost-Effectiveness of Lorlatinib for the Treatment of Adult Patients with Anaplastic Lymphoma Kinase Positive Advanced Non-Small Cell Lung Cancer in Spain - Presa M; Vicente D; Calles A; Salinas-Ortega L; Naik J; García LF; Soto J (Dove Medical Press, 2023)
María Presa,1 David Vicente,2 Antonio Calles,3 Laura Salinas-Ortega,1 Jaesh Naik,4 Luis F García,5 Javier Soto6 1Health Economics, Pharmacoeconomics and Outcomes Research Iberia (PORIB), Madrid, Spain; 2Medical Oncology Department, Hospital Universitario Virgen de Macarena, Sevilla, Spain; 3Medical Oncology Department, Hospital General Universitario Gregorio Marañon, Madrid, Spain; 4Health Economics, BresMed Health Solutions, Sheffield, UK; 5Oncology Medical, Pfizer, Madrid, Spain; 6Health Economics & Outcomes Research, Pfizer, Madrid, SpainCorrespondence: María Presa, Pº Joaquín Rodrigo 4- letra I, Pozuelo de Alarcón, Madrid, 28224, Spain, Tel +34 917 157 147, Email mpresa@porib.comPurpose: The objective of the present study was to evaluate the efficiency of lorlatinib compared to alectinib and brigatinib for the treatment of adult patients with anaplastic lymphoma kinase (ALK)-positive advanced non-small cell lung cancer (NSCLC) previously not treated, in Spain.Methods: A partitioned survival model comprised progression free, non-intracranial progression, intracranial progression, and death health states was constructed to estimate the total costs, life-years gained (LYG) and quality-adjusted life years (QALYs) accumulated in a lifetime horizon. Overall survival (OS) and progression-free survival (PFS) for lorlatinib were obtained from the CROWN study. For alectinib and brigatinib, a network meta-analysis of randomized controlled trials was conducted to estimate OS and PFS hazard ratios versus crizotinib. Utilities were estimated based on EQ-5D-5L data derived from the CROWN (lorlatinib), ALEX (alectinib) and ALTA-1L (brigatinib) studies. According to the Spanish National Health Service perspective the total costs (expressed in euros using a 2021 cost year) included drug acquisition and the administration's subsequent treatment, ALK+ advanced NSCLC management and adverse-event management, and palliative care. Unitary costs were obtained from local cost databases and literature. Costs, LYGs and QALYs were discounted at 3% annually. Deterministic and probabilistic sensitivity analyses were used to test the model's robustness.Results: Lorlatinib provided higher health outcomes (+0.70 LYG/patient, +1.42 QALYs/patient) and lower costs (-€ 9239/patient) than alectinib. Lorlatinib yielded higher LYG (+1.74) and QALYs (+2.30) versus brigatinib but higher costs/patient (+€ 36,627), resulting in an incremental-cost-effectiveness-ratio of € 15,912/QALY gained.Conclusion: The results of this study suggest that lorlatinib may be a dominant treatment option versus alectinib. Considering a willingness-to-pay threshold of € 25,000/QALY, lorlatinib may be an efficient option compared to brigatinib.Keywords: advanced non-small cell lung cancer, lorlatinib, ALK+, cost-effectiveness analysis, cost-utility analysis